CLIENT-SIDE ONLINE GAMBLING DETECTION USING MULTI-LAYER CASCADE PATTERN MATCHING IN MANIFEST V3 CHROME EXTENSIONS - Wingga Aria Sasra; Ahmad Abdul Chamid; Ahmad Jazuli (Jurnal Riset Informatika, 2026)
Online gambling sites in Indonesia generated IDR 155.4 trillion in transactions in 2025 with 3.2 million active players, yet DNS filtering the dominant countermeasure blocks only 0.64% of observed gambling traffic. Network-layer approaches fail structurally: they cannot intercept content via VPN, DNS-over-HTTPS, or direct IP access, and they cannot detect the domain neutralization used by the majority of Indonesian gambling operators. This paper proposes GUPI (Gambling URL Pattern Interceptor), a Chrome Extension implementing a three-layer cascade detection architecture running entirely client-side under Manifest V3 without external server dependencies. Layer 1 applies weighted lexical scoring to URL features. Layer 2 applies DOM keyword pattern matching with conditional context suppression. Layer 3 applies CSS selector-based DOM structural heuristic scoring to detect gambling-characteristic page architectures when text-level signals are absent. GUPI was evaluated on 926 URLs (326 gambling, 600 benign) across three sequential configurations. The full system achieves 98.81% accuracy, 99.07% precision, 97.55% recall, 98.30% F1-score, and 0.50% false positive rate.